Green(ing) of Transport Chains : Implications to Business Models - Heikkilä, Marikka; Edelman, Kristel; Franzén, Riikka (Slovenia, 2025)
This paper examines the transformation of business models in green transport through a case study involving cargo owners, land transport operators, and shipping companies. The study identifies four key themes driving green transport: commitment, collaboration, technology, and customer value, and examines how these themes shape emerging business models in the logistics sector. The findings reveal that leading companies are committing to better-than-regulation-standards. The study highlights the critical role of stakeholder collaboration in sharing infrastructure investments and risks, particularly in developing charging networks and renewable fuel supply chains. While market demand for green logistics is growing, especially among larger customers, the significant price premium for sustainable solutions remains a key challenge. The research indicates that business model transformation requires both technological innovation and new pricing strategies that balance cost with market acceptance. However, challenges such as inconsistent definitions of “green logistics” persist. This study contributes to the understanding of how logistics companies can effectively transition to sustainable operations while maintaining economic viability.
38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings